Machinability of metal matrix composites - Zhong, Chonghua. (2009)
Metal matrix composites (MMC) have been available for decades. Although previous work mainly was focused on processing of the materials, growing usage of MMCs requires understanding of secondary processes such as casting and machining. Conventional machining methods often result in cracking, splintering and pulling out of reinforcement particles. Non-conventional machining methods such as laser, electrical discharge machining (EDM) and abrasive water jet (AWJ) have proven to be applicable to MMCs. However, the rough surface finish and defects of component dramatically reduce the strength and could lead to early catastrophic failures. A proper method to obtain good surface finish is crucial to the application of the material.